Global 2000 techniques help to increase yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Global 2000, the 'green revolution' programme founded by former US President Jimmy Carter to control the causes of Africa's food shortages, is helping to increase dramatically maize and sorghum yields. The programme, now well established in Ghana...